Program Literasi Alam untuk Meningkatklan Pemahaman Lingkungan di Kalangan Pelajar Sekolah Dasar di Desa Dalu 10A Tanjung Morawa - Cut Zahara Salidia Sabrina; Revita Sari (Lembaga Pengembangan Kinerja Dosen, 2025)
The 2025 Independent Community Service Program (KKN) of the University of Muhammadiyah North Sumatra will be held in Dalu 10A Village, Tanjung Morawa District, Deli Serdang Regency. This activity aims to increase the understanding and concern of elementary school students for the environment through the natural literacy program. The educational approach is carried out through organic and inorganic waste introductions, recycling of used goods, and planting plant seeds in the school environment. In addition, students also carry out supporting activities such as financial management education, MSME promotion, and socialization of the importance of investment for students. To strengthen student understanding, the KKN team also prepared simple learning media in the form of posters and mini modules that make it easier for students to recognize the types of waste and simple steps to maintain cleanliness. The school is also involved through routine coordination to ensure the sustainability of the program after the KKN is completed. The results of the implementation show an increase in student awareness in maintaining school cleanliness, the emergence of environmentally caring behaviors, and the active involvement of the community and the school in maintaining the sustainability of the program. Overall, this KKN program has succeeded in fostering the value of social responsibility, ecological concern, and strengthening synergy between students, schools, and village communities in supporting a cleaner and more educational environment.